Perspectives of The Community Regarding Electronic-Based Dengue Vector Surveillance in the COVID-19 Pandemic - Aryani Pujiyanti; Wiwik Trapsilowati (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Penjaga is a google form-based application that helps families share their weekly larva monitoring data online. A study of community perceptions of the Penjaga application needs to be carried out to see the advantages and barriers to its implementation. This study measures the response rate and the public's perception of the online larva monitoring application.Method: The study used a cross-sectional design. Data were collected through an online survey involving 284 households in RW 3 and 7 in the South Rejowinangun Village, Magelang City, Central Java Province, in 2021. The online questionnaire includes questions about demographic information, perceptions of the application (convenience of use, duration of use, appearance, and benefits for preventing dengue), barriers to use, and suggestions for application improvement. Data analysis was done descriptively using the Product-Moment correlation statistical test. Results: Most respondents (59.5%) were female and 56.3% had completed their senior high education. Most of the respondents were in their pre-retirement and middle-aged. An average response rate of 86.3 % indicated that the family answered the application questions satisfactorily. The response rate dropped by 5.8 % when the health cadres released the application assistance. The community views the Penjaga application as user-friendly, quick, easy to use and learn, practical, and fascinating. The three most common challenges are the lack of respondents’ cell phone data quota and familiarity with Android devices. This study encourages health cadres to use the app, especially for elderly and non-mobile phone-owning families.